PFAS bioaccumulation in Antarctic breeding south polar skua (Catharacta maccormicki) and its prey items - Alfaro Garcia, Laura Andrea; Borgå, Katrine (Universitetet i Oslo, 2018)
Per- og polyfluorerte alkylstoffer (PFAS) har blitt funnet i blodprøver fra sørjo (Catharacta maccormicki) tatt i løpet av hekkesesongen i kolonien i Svarthamaren (Dronning Mauds land, Antarktis). For å undersøke om disse konsentrasjonene i sørjo stammer fra dietten i hekkesesongen, sammenligner denne oppgaven biomagnifisering i to næringskjeder. Ved innenlands kolonien Svarthamaren spiser sørjoene nesten utelukkende egg og unger fra antarktisk petrell (Thalassoica antarctica), og petrellene spiser fisk og krepsdyr. I den kystnære kolonien ved Dumont D’Urville (DDU, Adélie Land), spiser sørjoene hovedsakelig egg og unger fra Adélie pingviner (Pygoscelis adeliae). Væskekromatografi-massespektrometri (LC/MS) ble brukt for å måle PFAS i mageinnhold og egg fra antarktisk petrell, og i blodprøver fra sørjo, Adélie pingvin-unger, og antarktisk petrellunger og -voksne. Stabile isotoper (δ13C and δ15N) ble også analysert som diettdeskriptorer. Resultatene ble slått sammen med resultater fra tidligere studier fra begge koloniene for å oppnå et datasett for sørjo og dens diett ved både Svarthamaren og DDU. Datasettet ble brukt for å beregne biomagnifiseringsfaktor (BMF) og trofisk magnifisering faktor (TMF) for de detekterte PFASene i de to næringskjedene. Ved Svarthamaren var PFUnA over deteksjonsgrensen i alle matriksene, men var ikke tilstede i enkelte prøver. Andre detekterte PFASer var Perfluoroktyl sulfonat (PFOS), Perfluorononanoate (PFNA), Perfluorodecanoate (PFDcA), Perfluoroundecanoate (PFUnA), Perfluorododecanoate (PFDoA), Perfluorotridecanoate (PFTriA) and Perfluorotetradecanoate (PFTeA). PFAS konsentrasjonene økte oppover i næringskjeden, hvorav nivåene for alle detekterte PFASer var høyest hos sørjo. Ved DDU var PFAS konsentrasjonene lavere, men mønsteret var sammenlignbart med det i Svarthamaren. Forgrenet PFOS ble kvantifisert i sørjo fra DDU, men var ikke over deteksjonsgrense i andre matrikser. Byttedyrene hadde flere PFASer over deteksjonsgrensen i Svarthamaren sammenliknet med DDU. Vi beregnet BMF og TMF for alle detekterte PFASer i Svarthamaren, men kun for PFOS, PFNA, PFDcA og PFUnA i DDU fordi bare disse ble funnet i både sørjo og pingvinene. BMF for PFOS var høyere enn forventet i vanlige predator-bytte forhold i begge koloniene, noe som peker på en ukjent kilde. Biomagnifikasjonsverdiene for andre PFASer var varierende, men sammenliknbare mellom koloniene. PFAS-konsentrasjonene i sørjo fra begge kolonier og i antarktisk petrell reflekterer sannsynligvis eksponering utenfor Antarktis i løpet av vinteren. De detekterte konsentrasjoner i Adélie pingviner er ikke høye nok for å forklare de høye PFAS-nivåene i sørjoene i DDU. Derfor, i DDU, disse PFAS-nivåer kommer fra andre byttedyr enten innenfor regioner eller mest sannsynligvis fra utenfor Antarktis.
Keywords: Dronning Maud Land; kjemiske analyser; ornitologi; petreller; pingviner; sjøfugler; toksikologi

Bioaccumulation of Per and Polyfluoroalkyl Substances in Antarctic Breeding South Polar Skuas (Catharacta maccormicki) and Their Prey - Alfaro Garcia, Laura Andrea; Descamps, Sébastien; Herzke, Dorte; Chastel, Olivier; Carravieri, Alice; Cherel, Yves; Labadie, Pierre; Budzinski, Hélène; Munoz, Gabriel; Bustamante, Paco; Polder, Anuschka; Gabrielsen, Geir Wing; et al. (Frontiers in Marine Science, 2022)
Per and polyfluoroalkyl substances (PFASs) are found in Antarctic wildlife, with high levels in the avian top predator south polar skua (Catharacta maccormicki). As increasing PFAS concentrations were found in the south polar skua during the breeding season in Antarctica, we hypothesised that available prey during the breeding period contributes significantly to the PFAS contamination in skuas. To test this, we compared PFAS in south polar skuas and their main prey from two breeding sites on opposite sides of the Antarctic continent: Antarctic petrel (Thalassoica antarctica) stomach content, eggs, chicks, and adults from Svarthamaren in Dronning Maud Land and Adélie penguin chicks (Pygoscelis adeliae) from Dumont d’Urville in Adélie Land. Of the 22 PFAS analysed, seven were present in the majority of samples, except petrel stomach content [only perfluoroundecanoate (PFUnA) present] and Adélie penguins (only four compounds present), with increasing concentrations from the prey to the skuas. The biomagnification factors (BMFs) were higher at Dumont d’Urville than Svarthamaren. When adjusted to reflect one trophic level difference, the BMFs at Svarthamaren remained the same, whereas the ones at Dumont d’Urville doubled. At both the colonies, the skua PFAS pattern was dominated by perfluorooctanesulfonic acid (PFOS), followed by PFUnA, but differed with the presence of branched PFOS and perfluorotetradecanoate (PFTeA) and lack of perfluorononanoate (PFNA) and perfluorodecanoate (PFDA) at Dumont d’Urville. At Svarthamaren, the pattern in the prey was comparable to the skuas, but with a higher relative contribution of PFTeA in prey. At Dumont d’Urville, the pattern in the prey differed from the skuas, with the domination of PFUnA and the general lack of PFOS in prey. Even though the PFAS levels are low in Antarctic year-round resident prey, the three lines of evidence (pattern, BMF difference, and BMF adjusted to one trophic level) suggest that the Antarctic petrel are the significant source of PFAS in the Svarthamaren skuas, whereas the skuas in Dumont d’Urville have other important sources to PFAS than Adélie penguin, either in the continent or external on the inter-breeding foraging grounds far from Antarctica.
Keywords: Antarktis; fugler; miljøgifter; økotoksikologi

Bioaccumulation of Per and Polyfluoroalkyl Substances in Antarctic Breeding South Polar Skuas (Catharacta maccormicki) and Their Prey - Alfaro Garcia, Laura Andrea; Descamps, Sébastien; Herzke, Dorte; Chastel, Olivier; Carravieri, Alice; Cherel, Yves; Labadie, Pierre; Budzinski, Hélène; Munoz, Gabriel; Bustamante, Paco; Polder, Anuschka; Gabrielsen, Geir Wing; et al. (Frontiers in Marine Science, 2022)
Per and polyfluoroalkyl substances (PFASs) are found in Antarctic wildlife, with high levels in the avian top predator south polar skua (Catharacta maccormicki). As increasing PFAS concentrations were found in the south polar skua during the breeding season in Antarctica, we hypothesised that available prey during the breeding period contributes significantly to the PFAS contamination in skuas. To test this, we compared PFAS in south polar skuas and their main prey from two breeding sites on opposite sides of the Antarctic continent: Antarctic petrel (Thalassoica antarctica) stomach content, eggs, chicks, and adults from Svarthamaren in Dronning Maud Land and Adélie penguin chicks (Pygoscelis adeliae) from Dumont d’Urville in Adélie Land. Of the 22 PFAS analysed, seven were present in the majority of samples, except petrel stomach content [only perfluoroundecanoate (PFUnA) present] and Adélie penguins (only four compounds present), with increasing concentrations from the prey to the skuas. The biomagnification factors (BMFs) were higher at Dumont d’Urville than Svarthamaren. When adjusted to reflect one trophic level difference, the BMFs at Svarthamaren remained the same, whereas the ones at Dumont d’Urville doubled. At both the colonies, the skua PFAS pattern was dominated by perfluorooctanesulfonic acid (PFOS), followed by PFUnA, but differed with the presence of branched PFOS and perfluorotetradecanoate (PFTeA) and lack of perfluorononanoate (PFNA) and perfluorodecanoate (PFDA) at Dumont d’Urville. At Svarthamaren, the pattern in the prey was comparable to the skuas, but with a higher relative contribution of PFTeA in prey. At Dumont d’Urville, the pattern in the prey differed from the skuas, with the domination of PFUnA and the general lack of PFOS in prey. Even though the PFAS levels are low in Antarctic year-round resident prey, the three lines of evidence (pattern, BMF difference, and BMF adjusted to one trophic level) suggest that the Antarctic petrel are the significant source of PFAS in the Svarthamaren skuas, whereas the skuas in Dumont d’Urville have other important sources to PFAS than Adélie penguin, either in the continent or external on the inter-breeding foraging grounds far from Antarctica.
Keywords: Antarktis; Dronning Maud Land; biologi; ornitologi; petreller; sjøfugler